3 reasons why campus concert guidelines suck - Mohd Azmyl, Md Yusof * (The Malaysian Insight, 2023)
UNIVERSITIES in Malaysia are pretty boring. Even the private ones. They are devoid of life, culture, and excitement unless you like the food and beverage stalls or promotional booths (especially of telcos) that are set up during events.